Bimetallic platinum-rhodium nanocomposites for dimethylamine borane dehydrogenation: an experimental and density functional theory study - Alptekin, Oznur; Sen, Betul; Acidereli, Hilal; Ercetin, Umran; Fellah, Mehmet Ferdi; Sen, Fatih (Royal Soc Chemistry, 2020)
In this study, bimetallic platinum-rhodium nanocomposites supported on graphene oxide (PtRh@GO) were synthesized and used as a catalyst in the dimethylamine borane (DMAB) dehydrogenation. The synthesized PtRh@GO catalyst was characterized using spectral and microscopic methods. The characterization studies revealed that the obtained PtRh@GO nanomaterials were nano-sized and exhibited a monodisperse distribution on GO. As a result of the catalytic studies, it was determined that the dehydrogenation reaction of dimethylamine borane depends on the temperature, amount of catalyst, and substrate. Additionally, some kinetic data and activation parameters were investigated for the dimethylamine dehydrogenation of DMAB with the help of PtRh@GO. The kinetic and activation parameters showed that the PtRh@GO catalyst could be used effectively. The activation energy (E-a) was found to be 17 +/- 2 kJ mol(-1)for the dimethylamine borane dehydrogenation. Using previously performed studies, comparison studies for the turnover frequency (TOF) value of the PtRh@GO catalyst in the dimethylamine borane reaction showed that the obtained PtRh@GO catalyst could be used effectively with a higher TOF (274.6 h(-1)) value. In addition, DFT computations were utilized on the structure of PtRh@GO in order to investigate the activity of the catalyst. The experimental data have been supported by the theoretical results based on DFT.
Keywords: [No Keywords]